Cha-Cha Thrifting: vintage clothing / Danial Hakim Amer Ludin ... [et al.] - Amer Ludin, Danial Hakim; Mohd Ramzi, Danial Hakim; Jumawan, Nor Nasha Izzaty; Azlan, Nur Azlin; Mohd Firdaus Victor, Adam Aiqmal (2021)
Cha-Cha Thrifting is a vintage clothing bundle business that provides beautiful quality clothing even if it is old clothing. This is because we want customers to be satisfied with the products we provide. Our target customers are teenagers and our clothes are also unisex where men and women can wear them. In addition, Cha-Cha Thrifting is a partnership business consisting of 5 partners namely Danial Hakim Bin Amer Ludin as General Manager, Nur Azlin Binti Azlan as Administration Manager, Danial Hakim Bin Mohd Ramzi as Marketing Manager, Nor Nasha Izzaty Binti Jumawan as Operation Manager and Adam Aiqmal Bin Mohd Firdaus Viktor as Financial Manager. Everyone has a different role in this business. Cha-Cha Thrifting's partner is a person who is skilled in the field of business and helps a lot in growing the business as well as running the business effectively and efficiently. Apart from that, the location of the store we chose is also very helpful in our business because it is located in the city of Shah Alam, Selangor. Finally, we hope that our business meets the needs of customers who are very interested in vintage clothing. Next, we also want to provide the best service to customers.